Exploring Factors Influencing Zakat Compliance in Aceh: The Role of Institutional Trust and Religious Commitment - Evriyenni, Evriyenni; Fahlevi, Heru; Indriani, Mirna; Yusuf, Muhammad Yasir (SCAD Independent, 2025)
Zakat compliance among Indonesian Muslims remains relatively low despite its mandatory under Islamic law and regional regulations. This study investigates the factors influencing zakat compliance in Aceh Province, Indonesia, by examining the roles of accountability, financial report transparency, institutional credibility, religiosity, and zakat literacy. It also explores the mediating role of muzakki’s interest in enhancing compliance through formal Zakat Institutions, specifically Baitul Mal. Data were collected from 500 muzakki across 23 regencies/ cities using online and on-site surveys. Employing Structural Equation Modeling and Partial Least Squares (SEM-PLS), the results reveal that accountability and transparency significantly affect muzakki’s interest, influencing zakat compliance. Moreover, accountability, transparency, religiosity, and muzakki’s interest directly affect compliance, while institutional credibility and zakat literacy show limited impact. This study offers practical implications for strengthening local zakat management systems. It contributes to the broader discourse in Islamic social finance by providing an empirical model applicable to other Muslim-majority contexts to improve formal zakat governance and behavioral compliance.